Using a Triple Graph Grammar for State Machine Implementations - Striewe, Michael; Goedicke, Michael (Electronic Communications of the EASST, 2009)
Typical techniques of model-driven development use graph transformations to manipulate models and use generators to produce source code. In this contribution we suggest to use graph transformations instead of generators in order to get a closer connection between model and code. We define a Triple Graph Grammar for the mapping from a modeling tool data format to source code and derive a sample set of transformation rules from this. Thereby both truly simultaneous manipulation of model and code is enabled as well as virtually simultaneous manipulation by direct propagation of changes from code to model and back again.